Kepemimpinan Kepala Madrasah Dalam Mengembangkan Sarana Prasarana MAN 3 Banyuwangi - Eko Budiywono; Khoirul Fahmi Iskandar (Institut Agama Islam Darussalam Blokagung, 2020)
The research objectives of this study were (1) to determine the infrastructure in MAN 3 Banyuwangi, (2) to determine the leadership of the head of the madrasah in developing the infrastructure for MAN 3 Banyuwangi, and (3) to determine the supporting and inhibiting factors of the headmaster's leadership in developing the facilities. infrastructure in MAN 3 Banyuwangi. This research uses descriptive qualitative research. In this study, data collection techniques used observation, interviews, and documentation. Meanwhile, data analysis in this study used interactive analysis with 3 models of Miles & Huberman, including: (1) data reduction, (2) data presentation and (3) decision making. The results of this study (1) the current madrasah infrastructure is classified as good and sufficient for the infrastructure needs, (2) the strategy of the madrasah principal in developing infrastructure by managing funds from the government and funds from infaq students or guardians of students, (3) ) Supporting factors in developing school infrastructure, principals and infrastructure have full policies in developing, maintaining and maintaining existing infrastructure and cooperation of all elements of the teacher council, employees and even students. Meanwhile, the inhibiting factor is due to the very limited budget owned by the school.